Institutional Certification for Personal Trainers in Angola.An Alternative for Professionalization Favoring Public Health - Gómez Barrios, Summar Alfredo (Revista Internacional de Pedagogía de la Actividad Física y Deporte, 2026)
The purpose of this article is to analyze the managerial culture of sport in Ecuador, emphasizing high performance and neighborhood leagues. The research involved conducting in-depth interviews with key people who hold management positions in these sports segments, which is why the methodology was based on a qualitative, descriptive and field approach, materialized in the method of grounded theory. The results revealed that there is a managerial task that to a large extent is exercised without the necessary professional, technical and human skills, with weaknesses in academic training and with little training in the managerial area. It is concluded that these factors, properly aligned with effective actions and under a shared destiny, would guarantee a successful performance, in order to direct the Ecuadorian sport to better results at the local, regional and international level.